Relação entre a taxa de vacinação contra brucelose bovina, frente à classificação de risco para febre aftosa np Estado do Pará: Andréa Ferreira Nobre. - - Nobre, Andréa Ferreira [UNESP] (2013)
The brucellosis and foot and mouth disease (FMD) are two economically important diseases affecting cattle that have as a major control measure compulsory vaccination and transit control. The marketing of animals and animal products within the country and to other countries is based on sanitary status in relation to FMD and the Pará State was divided, in 2008, into three areas - free of disease with vaccination (1), medium risk (2) and high risk (3). In 2010 there was a change in that classification and area 3 also went for medium risk. Considering that, trade and transit of cattle and buffaloes is only possible by mean of the compulsory vaccination of females against brucellosis, the aim of this study was to evaluate if there was any relation between the rate of brucellosis vaccination recommended by the National Program for Control and Eradication of Brucellosis and Tuberculosis (PNCEBT) and the areas delimited by the National FMD Eradication Program (PNEFA). The data vaccination from the herd used for the analysis consisted of the vaccination percentage (number of vaccinated/ total number) of females with 3-8 months old, during the years fo 2008 and 2011. In 2008, areas 1, 2 and 3 had an average vaccination rate of 36.3%, 25.3% and 22.5%, respectively, with significant difference between area 1 and the other. In 2011 there was a significant increase in immunization rates in all areas, observing averages of 61.7%, 50.9% and 48.3% respectively, without statistical difference. The percentage of municipalities within the free area with immunization rates above 80%, increased from 11.36% in 2008 to 58.3% in 2011 (up 5.1 times), the same as area 2, which increased from 3. 92% to 31.3% of the municipalities (8 times) and the area 3, that increased from 0% to 28%. The whole state had increased mean vaccination rates over time...